2006
DOI: 10.1016/j.jvs.2006.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Progression of atherosclerotic renovascular disease: a prospective population-based study

Abstract: This is the first prospective, population-based estimate of incident RVD and progression of prevalent RVD among free-living elderly Americans. In contrast to previous reports among select hypertensive patients, CHS participants with a low rate of clinical hypertension demonstrated a significant change of RVD in only 14.0% of kidneys on follow-up of 8 years (annualized rate, 1.3% per year). Progression to significant RVD was observed in only 4.0% (annualized rate, 0.5% per year), and no prevalent RVD progressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 39 publications
(49 reference statements)
0
27
1
4
Order By: Relevance
“…In contrast to previous reports among selected patients with hypertension, these participants had a low frequency of hypertension and an annualized rate of only 1.3% per year for significant RAS and 0.5% per year for progression to significant RAS as no prevalent RAS progressed to occlusion over 8 years. 176 The risks of RAS are related both to declining kidney function and to accelerated CVD, with increased morbidity and mortality. 177 Recent studies reemphasize the predictive value of clinical variables, including age, symptomatic vascular disease, elevated serum cholesterol, and presence of abdominal bruit, as the most powerful predictors of detecting lesions of at least 50% stenosis.…”
Section: Renal Artery Stenosismentioning
confidence: 99%
“…In contrast to previous reports among selected patients with hypertension, these participants had a low frequency of hypertension and an annualized rate of only 1.3% per year for significant RAS and 0.5% per year for progression to significant RAS as no prevalent RAS progressed to occlusion over 8 years. 176 The risks of RAS are related both to declining kidney function and to accelerated CVD, with increased morbidity and mortality. 177 Recent studies reemphasize the predictive value of clinical variables, including age, symptomatic vascular disease, elevated serum cholesterol, and presence of abdominal bruit, as the most powerful predictors of detecting lesions of at least 50% stenosis.…”
Section: Renal Artery Stenosismentioning
confidence: 99%
“…32 Buller et al 17 found that creatinine clearance showed an independent and continuous relationship with the frequency of RAS. In a recent prospective study, a lower rate of RAS progression was reported in elderly patients; 33 however, most studies point to a progressive worsening of RAS as a typical course in the natural history of RAS. In a study by Zierler et al, 34 42% of patients with RAS showed progression of RAS over the 2-year follow-up period, and 11% eventually progressed to occlusion.…”
Section: Discussionmentioning
confidence: 93%
“…Стеноз почечных артерий атеросклеротической этиологии встречается относительно часто, особенно у больных старческого возраста, но редко прогресси-рует до АГ или почечной недостаточности [640]. Про-должает дебатироваться вопрос, целесообразно ли выполнять больным АГ или почечной недостаточно-стью такие вмешательства, как (чаще всего) чрескож-ное стентирование почечной артерии.…”
Section: реноваскулярная гипертонияunclassified